Six Sigma quality for business & manufacture - Gordon, M. Joseph (Elsevier, 2002)
Six Sigma is Business and Industry's newest recognized quality program. This text provides information and instructions for new and current quality professionals in order to help employ methods to attain Six Sigma defect quality assurance within their company. All areas of business and manufacture are covered. Detailed checklists, questionnaires and forms assist personnel in developing their own programs to 'prevent' problems from occurring and to solve new and long-term problems in services and manufacturing. Examples and formulae are provided for use to determine if, when and then how much a process may be adjusted for reaching higher quality assurance levels. Knowledgeable readers will be able to use this comprehensive text immediately in the workplace.